2007
DOI: 10.2165/00019053-200725090-00002
|View full text |Cite
|
Sign up to set email alerts
|

The Increasingly Complex Fourth Hurdle for Pharmaceuticals

Abstract: There are three known criteria that underlie drug reimbursement decisions: therapeutic value, cost effectiveness and burden of disease. However, evidence from recent reimbursement decisions in several jurisdictions points to residual unexplained variables, one of which may be budget impact. An economic rationale for carrying out budget impact analyses is opportunity cost, measured by the economic benefits foregone by using resources in one way rather than another. Under certain assumptions, cost-effectiveness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 30 publications
2
27
0
Order By: Relevance
“…In general, however, decision-makers do not use explicit threshold ICER values because they wish to take into account all relevant considerations as well as cost-effectiveness [25,26]. In addition, without sufficient justification for increased efficiency, the use of a single threshold value could increase pharmaceutical spending [27,28]. HIRA decided not to set a threshold value, but to consider per capita GDP [29] as a reference value and make flexible judgments based on disease severity, societal burden, quality of life, and the innovative nature of submissions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, however, decision-makers do not use explicit threshold ICER values because they wish to take into account all relevant considerations as well as cost-effectiveness [25,26]. In addition, without sufficient justification for increased efficiency, the use of a single threshold value could increase pharmaceutical spending [27,28]. HIRA decided not to set a threshold value, but to consider per capita GDP [29] as a reference value and make flexible judgments based on disease severity, societal burden, quality of life, and the innovative nature of submissions.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, assessments of cost-effectiveness and budget impact might have produces contradictory information for decision makers. For example, CEA may indicate an efficient technology but budget impact analysis (BIA) results indicate that it may not be affordable [28], and as yet, there is no scientific guidance as to how to resolve this dilemma [30]. Under the current PLS, these two factors will maintain their importance as decision criteria, and thus, HIRA attempts to balance potentially contradictory information by considering the nature of the drug and of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…The objective is to make the most efficient use of resources in line with economic theory to cancel funding for pharmaceuticals that are no longer seen as cost-effective, and transferring the resources released to fund technologies including new drugs that enhance the level of health gain efficiently [17]. The TLV has divided all existing drugs into 49 groups based on their Anatomical Therapeutic Chemical (ATC) classification [13,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Accounting for criteria such as burden of disease and availability of treatment alternatives, three studies identified that NICE's willingness to pay is a little higher than suggested [25][26][27]. Dakin et al demonstrated that differentiation is required between unrestricted and restricted coverage, which depended on the number of randomized controlled trials, systematic reviews, the timing of the decision and the presence of a patient group submission [25,28]. Jena and Philipson showed that, besides costeffectiveness, the probability of a positive recommendation was influenced by the type of technology [27].…”
Section: Scope Of Analysismentioning
confidence: 99%